Session-RPE for quantifying the load of different youth basketball training sessions - C Lupo; A Tessitore; L Gasperi; MAR Gomez (Termedia Publishing House, 2016)
The aim of the study was to evaluate youth basketball training, verifying the reliability of the session-RPE method in relation to session duration (< and ≥ 80 minutes) and workout typology (reduced and high warm-up, conditioning, technical, tactical, game portions within a single session) categories. Six male youth basketball players (age, 16.5±0.5 years; height, 195.5±6.75 cm; body mass, 93.9±10.9 kg; and body mass index, 23.6±2.8 kg.m-2) were monitored (HR, type and duration of workouts) during 15 (66 individual) training sessions (80±26 minutes). Edwards' HR method was used as a reference measure of internal training load (ITL); the CR-10 RPE scale was administered 30 minutes after the end of each session. The results obtained showed that all comparisons between different session durations and workout portions revealed effects in term of Edwards' ITLs except for warm-up portions. Moderate to strong relationships between Edwards' and session- RPE methods emerged for all sessions (r = .85, P < .001), player's sessions (r range = .79 - .95, P < .001), session durations (< 80 minutes: r = .67, P < .001; ≥ 80 minutes: r = .75, P < .001), and workout portions (r range = .78 - .89, P range = .002 - < .001). The findings indicated that coaches of youth basketball players can successfully use session-RPE to monitor the ITL, regardless of session durations and workout portions.